Confidence in dementia care and care approach toward dementia among the nursing staff in long-term care facilities in China: a cross-sectional survey - Chen, Haiwen; Song, Jie; Zhang, Nan; Li, Na; Jiang, Qianqian; Lu, Xiaohan; Liu, Lin; Liu, Yue (Frontiers in Public Health, 2023)
Abstract Background: Confidence and appropriate care approach toward dementia among nursing staff (nurses and care assistants) are crucial manifestations of competency to deal with the complexity of dementia care in long-term care facilities (LTCFs). The purpose of this study was to investigate the confidence in dementia care and care approach among nursing staff in LTCFs in mainland China. Methods: A cross-sectional study design was utilized in LTCFs in Shandong Province, mainland China. A convenient sample included of 317 nursing staff drawn from 15 LTCFs. Survey questions included (a) demographics, (b) dementia knowledge, (c) dementia care confidence and (d) approach to care for people with dementia. Data were analyzed with descriptive statistics. Factors associated with confidence and care approach for people with dementia were examined using Pearson’s correlation and multivariate regression analyses. Results: Dementia care confidence was generally moderate. Factors affecting confidence to care for people with dementia included educational level, months of caring dementia patients, and dementia knowledge. Most nursing staff did not use a person-centered care approach which was significantly associated with their age, dementia-learning experience, and knowledge and confidence toward caring for people with dementia. Conclusions: A positive correlation was identified between confidence to care for people with dementia and nursing staff’ care approach. Clinical recommendations are provided to further develop education strategies tailored for nursing staff to meet the growing demand for dementia care services.